Case Report: Swept-source Optical Coherence Tomography and Angiography Findings in Lipemia Retinalis. Issue 1 (6th January 2022) - Bouraoui, Rim; El Matri, Khaled; Derouiche, Kaouther; Falfoul, Yousra; Amrouche, Chiraz; Hachicha, Ines; Othmani, Emna; Mghaieth, Fatma; El Matri, Leila
Abstract : SIGNIFICANCE: Lipemia retinalis is a very rare ocular manifestation of severe hypertriglyceridemia. It is usually symptomatic and regresses after normalization of triglycerides levels. Early recognition is important to prevent ocular and life-threatening complications. PURPOSE: This study aimed to report a case of marked lipemia retinalis secondary to type V hypertriglyceridemia assessed with swept-source optical coherence tomography (OCT) and OCT angiography (OCT-A), with follow-up after dietary lipid restriction. METHODS: Observational case report of lipemia retinal findings on color fundus photography, swept-source OCT and OCT-A, initially and after triglycerides lowering. CASE REPORT: A 32-year-old pregnant patient with gestational diabetes and a history of hypertriglyceridemia was referred for diabetic retinopathy screening. Fundus examination revealed bilateral milky-white discoloration of retinal vessels with a "salmon-colored" retina. Swept-source OCT and OCT-A revealed extremely hyperreflective and dilated retinal vessels and multiple high-flow retinal hyperreflective dots, corresponding to dilated retinal capillaries. Choroidal vessels were enlarged and engorged, and choriocapillaris layer appeared thickened and hyperreflective with dilated and tortuous capillaries. Serum triglycerides were very high (70.02 mmol/L). After 21 days of very-low-fat diet, it was lowered to 15 mmol/L. We noted a normalization of the clinical, structural, and vascular findings. However, peripheral retinal vessels remained hyperreflective, despite their clinical normalization. CONCLUSIONS: Swept-source OCT and OCT-A were beneficial in assessing lipemia retinalis noninvasively and monitoring choroidal and retinal vascular changes. Lipemia retinalis signs regressed initially in the posterior pole, choroidal anomalies were first to resolve, and clinical normalization preceded tomographic resolution.